The Effects of Single and Bimetallic Silicon Composite Shields in Medical Imaging Methods: A Monte Carlo Study - Abbas Ali Nazeri; Reza Malekzadeh; Parinaz Mehnati; Soheila Refahi (Frontiers in Biomedical Technologies)
Purpose: Nowadays, the use of polymer composites with several metals to design and build new radiation composite shields with practical features in radiology is expanding.